Lower Baseline Serum Triglyceride Levels Are Associated With Higher Decrease in Body Mass Index After Laparoscopy Sleeve Gastrectomy Among Obese Patients - Huang, Xiu; Li, Guifang; Xu, Bei; Zhang, Junyi; Wang, Xingchun; Cheng, Xiaoyun; Jayachandran, Muthukumaran; Huang, Yueye; Qu, Shen (Frontiers in Endocrinology, 2021)
Aims To investigate the predictive value of baseline serum triglyceride (TG) levels for improvements of metabolism after laparoscopic sleeve gastrectomy (LSG). Methods 112 obese patients [body mass index (BMI) ≥ 35kg/m2] underwent LSG and with complete information of anthropometric and metabolic parameters were divided into normal TG group (group A) and high TG group (group B), while group A had TG levels ≤ 1.7 mmol/L, and group B had TG levels ＞ 1.7 mmol/L. The post-operative changes (Δ) in metabolic parameters between the two groups were compared. Results In the whole cohort, the metabolic parameters were significantly improved at 6 months after LSG. BMI and waist circumference (WC) decreased significantly in the two groups. The ΔBMI among group A and group B were 11.42±3.23 vs 9.13±2.77kg/m2 (p<0.001), respectively. ΔBMI was positively correlated with ΔWC (r=0.696, p<0.001), Δfasting insulin level (r=0.440, p=0.002), Δfasting serum C peptide level (r=0.453, p=0.002), and Δhomeostasis model assessment insulin resistance index (r=0.418, p=0.004) in group A. Compared with group B, group A had a significantly higher odds ratio (OR) of 2.83 ( 95% confidence interval [CI ]1.25-6.38, p=0.012）and 2.73 ( 95% CI 1.11-6.72, p=0.029 ) for ΔBMI and ΔWC after adjustment for age and gender, respectively. Conclusions Obese patients with baseline TG levels under 1.7 mmol/L had greater loss of weight at six months follow-up later LSG. This finding suggests that baseline TG level may have a predictive value for weight loss, at least in the short-term follow-up.